IMPROVING THE ETHOD OF MANAGING DATA ON THE LAND ACCOUNT WITH THE HELP OF A MOBILE APPLICATION - Turaev Rukhiddin Amirkulovich,; Tashbaeva Hulkaroy Kholmurod girl, (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
This article talks about the problems of improving the transmission of information about land in an interactive way today and its solution. There is talk of a mobile application that transmits data about users offline